1998
DOI: 10.1079/bjn19980026
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of β-carotene, lycopene and lutein in men and women following a standard meal: response curves in the triacylglycerol-rich lipoprotein fraction

Abstract: A high intake of fruit and vegetables is believed to be protective against heart disease and cancer. /3-Carotene has been closely examined for evidence of these protective properties but evidence is still conflicting and there are many other carotenoids in plant foods which deserve attention. This paper reports studies on the concentrations of lutein and lycopene in the triacylglycerol-rich lipoprotein (TRL) fraction of plasma in comparison with /?-carotene following a large dose of the respective carotenoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
87
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 30 publications
11
87
0
Order By: Relevance
“…Indeed it was shown that the extent of absorption of carotenoids was comprised of between 11% for all-trans ␤-carotene and 2.5% for all-trans lycopene. It is also in agreement with a study that estimated absorption efficiency from chylomicron response (32). With this method, it was estimated that 1.4 mg of 40 mg ␤-carotene (3.5%) and 1 mg of 40 mg lycopene (2.5%) were absorbed in humans, values close to the solubility values measured here, i.e., 4.8 and 2.0%.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed it was shown that the extent of absorption of carotenoids was comprised of between 11% for all-trans ␤-carotene and 2.5% for all-trans lycopene. It is also in agreement with a study that estimated absorption efficiency from chylomicron response (32). With this method, it was estimated that 1.4 mg of 40 mg ␤-carotene (3.5%) and 1 mg of 40 mg lycopene (2.5%) were absorbed in humans, values close to the solubility values measured here, i.e., 4.8 and 2.0%.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, lutein increased plasma β-carotene in five subjects but reduced it in three others. Recent work of our own also suggests that both lycopene (53 %) and lutein (38 %) may not be absorbed as efficiently as β-carotene (P < 0·05; Table 5; O'Neill & Thurnham, 1998).…”
Section: Absorption Of B-carotene and Its Conversion To Retinolmentioning
confidence: 99%
“…However, in two recent studies (Van Vliet et al 1995;O'Neill & Thurnham, 1998) in which very different large intakes of β-carotene were given (15 mg and 40 mg respectively) the mean absorption of β-carotene was < 2·0 mg, suggesting that the human intestine possesses only a limited capacity to absorb β-carotene. In both studies more than half the β-carotene absorbed was converted to retinol.…”
Section: Absorption Of B-carotene and Its Conversion To Retinolmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that lutein and b-carotene compete for absorption (Micozzi et al, 1992;Kostic et al, 1995;Albanes et al, 1997); however, the same is not necessarily true for lycopene and b-carotene. While some have shown enhanced b-carotene absorption with lycopene administration (High & Day, 1951), others have shown either no effect or inhibition on b-carotene absorption (White et al, 1993;Johnson et al, 1997;O'Neill & Thurnham, 1998). Therefore, the larger lycopene to b-carotene ratio present in the tomato paste may inhibit absorption of b-carotene.…”
Section: Discussionmentioning
confidence: 99%